PERANCANGAN ULANG STRATEGI PENJUALAN PADA BISNIS PERUMAHAN DALAM MENINGKATKAN MINAT BELI KONSUMEN - Sudewo; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2017)
Residential property sales prospects in particular has a huge opportunity from year to year because the value of the price of land has the ability to sell value increasing from year to year. Sales of residential house Fortuna Residence subdistrict area Bojonggede Bogor regency still have a business opportunity housing is very large, in addition to the quality and design of the house is sold, housing Fortuna Residence is very strategy that includes developing a connecting road Bogor regency so competitive very competitive , This research aims to design a sales strategy on housing Fortuna Residence with the results in the form of a SWOT strategy is based on statistical data processing with SEM (Structural Equation Modeling) where variables are used, there are five independent variables and the dependent variable. Variable independet have a positive and significant with the dependent variable, namely (1) the variable quality of the product has a positive and significant to the variable buying interest, (2) a variable pricing strategy has a positive and significant to the variable buying interest, (3) a variable transportation and the location has a positive and significant relationship to variable buying interest, (4) variable product innovation has a positive and significant relationship to variable buying interest, (5) variable sales promotion have a positive and significant relationship to the variable buying interest.